Effect of bariatric surgery on long-term cardiovascular outcomes: a nationwide nested cohort study. (19th March 2020) - Moussa, Osama; Ardissino, Maddalena; Heaton, Tobias; Tang, Alice; Khan, Omar; Ziprin, Paul; Darzi, Ara; Collins, Peter; Purkayastha, Sanjay
Abstract: Aims : This study aims to evaluate the long-term effect of bariatric surgery on cardiovascular outcomes of patients with obesity. Methods and results : A nested cohort study was carried out within the Clinical Practice Research Datalink. The study cohort included the 3701 patients on the database who had undergone bariatric surgery and 3701 age, gender, and body mass index-matched controls. The primary endpoint was the composite of fatal or non-fatal myocardial infarction and fatal or non-fatal ischaemic stroke. Secondary endpoints included fatal or non-fatal myocardial infarction alone, fatal or non-fatal ischaemic stroke alone, incident heart failure, and mortality. The median follow-up achieved was 11.2 years. Patients who had undergone bariatric surgery had a significantly lower occurrence of major adverse cardiovascular events [hazard ratio (HR) 0.410, 95% confidence interval (CI) 0.274–0.615; P < 0.001]. This was mainly driven by a reduction in myocardial infarction (HR 0.412, 95% CI 0.280–0.606; P < 0.001) and not in acute ischaemic stroke (HR 0.536, 95% CI 0.164–1.748; P = 0.301). A reduction was also observed in new diagnoses of heart failure (HR 0.403, 95% CI 0.181–0.897; P = 0.026) and mortality (HR 0.254, 95% CI 0.183–0.353; P < 0.001). Conclusion : The results of this large, nationwide cohort study support the association of bariatric surgery with lower long-term risk of major cardiovascular events and incident heart failure in patients with obesity.